Efficacy of antibiotic treatment of implant-associated Staphylococcus aureus infections with moxifloxacin, flucloxacillin, rifampin, and combination therapy: an animal study - Greimel F; Scheuerer C; Gessner A; Simon M; Kalteis T; Grifka J; Benditz A; Springorum HR; Schaumburger J (Dove Medical Press, 2017)
Felix Greimel,1 Christine Scheuerer,1 Andre Gessner,2 Michaela Simon,2 Thomas Kalteis,1 Joachim Grifka,1 Achim Benditz,1 Hans-Robert Springorum,1 Jens Schaumburger1 1Department of Orthopedics, University Medical Center Regensburg, Asklepios Klinikum Bad Abbach, Bad Abbach, 2Institute of Clinical Microbiology and Hygiene, University Medical Center Regensburg, Regensburg, Bavaria, Germany Abstract: The efficacy of antibiotic monotherapy and combination therapy in the treatment of implant-associated infection by Staphylococcus aureus was evaluated in an animal study. The femoral medullary cavity of 66 male Wistar rats was contaminated with S. aureus (ATCC 29213) and a metal device was implanted, of which 61 could be evaluated. Six treatment groups were studied: flucloxacillin, flucloxacillin in combination with rifampin, moxifloxacin, moxifloxacin in combination with rifampin, rifampin, and a control group with aqua. The treatment was applied for 14 days. After euthanasia, the bacterial counts in the periprosthetic bone, the soft tissue, and the implant-associated biofilm were measured. Both antibiotic combination treatments (moxifloxacin plus rifampin and flucloxacillin plus rifampin) achieved a highly significant decrease in microbial counts in the bone and soft tissue and in the biofilm. Mono-antibiotic treatments with either moxifloxacin or flucloxacillin were unable to achieve a significant decrease in microbial counts in bone and soft tissue or the biofilm, whilst rifampin was able to reduce the counts significantly only in the biofilm. Antibiotic resistance was measured in 1/3 of the cases in the rifampin group, whereas no resistance was measured in all other groups. The results show that combinations of both moxifloxacin and flucloxacillin plus rifampin are adequate for the treatment of periprosthetic infections due to infections with S. aureus, whereas monotherapies are not effective or not applicable due to the rapid development of antibiotic resistance. Therefore, moxifloxacin is an effective alternative in combination with rifampin for the treatment of implant-associated infections. Keywords: moxifloxacin, rifampin, flucloxacillin, implant-associated infection, prosthetic infection, Staphylococcus aureus